Large deflection of composite beams in bending - Teo, Chin Yao (Nanyang Technological University, 2021)
The goal of this project is to investigate large deflection response and behavior of composite beams. Composite beams are first fabricated out of AX-5112T, a bidirectional woven repreg. Three-point bending tests will be conducted at spans of 150mm, 175mm, and 200mm. Load and displacement data are extracted from the Instron-5569 and plots are to be made in excel using the extracted data. Further data such as bending stiffness, slip distance, and rotation angle at the support are derived from the extracted data. Previous final year reports done by Bao Fu and Tan Chun Siang made use of the unidirectional prepreg AX-6200C. Comparison will be made against these two final year reports. Comparisons will also made against plots using data derived from Jacobi functions using Maple. Recommendations of future studies will be made regarding the use of different materials and improvements to the test set up.